Candid Lame Ducks - Mariana Lopes da Fonseca (Center for Economic Studies and ifo Institute (CESifo), 2016)
This study relies on a recent reform introducing gubernatorial term limits at the Portuguese local level to explore how an exogenous variation in eligibility for re-election affects local fiscal policy choices. Relying on electoral and fiscal outcomes for the past three complete electoral terms and a quasi-experimental diff-in-diff approach, the empirical analysis estimates how fiscal policy differs on average between re-eligible and term-limited incumbents. Results indicate that rather than engaging in opportunistic behavior, lame ducks pursue more conservative fiscal policies. Term limited officeholders choose lower property tax rates and reduced levels of current expenditure relative to re-eligible incumbents. Heterogeneous effects further suggest that ineligible mayors behave more truthfully and do not engage in political business cycles, challenging previous results in the literature.
Keywords: D72; H11; 330; institutional reform; term limits; fiscal policy; municipal accounts